Artificial Liver Support Systems in Acute Liver Failure and Acute-on-Chronic Liver Failure: Systematic Review and Meta-Analysis - Brown, Robert S.; Fisher, Robert A.; Subramanian, Ram M.; Griesemer, Adam; Fernandes, Milene; Thatcher, William H.; Stiede, Kathryn; Curtis, Michael (Critical care explorations, 2025)
OBJECTIVES: To systematically review the safety and efficacy of nonbiological (NBAL) or biological artificial liver support systems (BAL) and whole-organ extracorporeal liver perfusion (W-ECLP) systems, in adults with acute liver failure (ALF) and acute-on-chronic liver failure (ACLF). DATA SOURCES: Eligible NBAL/BAL studies from PubMed/Embase searches were randomized controlled trials (RCTs) in adult patients with ALF/ACLF, greater than or equal to ten patients per group, reporting outcomes related to survival, adverse events, transplantation rate, and hepatic encephalopathy, and published in English from January 2000 to July 2023. Separately, we searched for studies evaluating W-ECLP in adult patients with ALF or ACLF published between January1990 and July 2023. STUDY SELECTION AND DATA EXTRACTION: Two researchers independently screened citations for eligibility and, of eligible studies, retrieved data related to study characteristics, patients and interventions, outcomes definition, and intervention effects. The Cochrane Risk of Bias 2 tool and Joanna Briggs Institute checklists were used to assess individual study risk of bias. Meta-analysis of mortality at 28-30 days post-support system initiation and frequency of at least one serious adverse event (SAE) generated pooled risk ratios (RRs), based on random (mortality) or fixed (SAE) effects models. DATA SYNTHESIS: Of 17 trials evaluating NBAL/BAL systems, 11 reported 28-30 days mortality and five reported frequency of at least one SAE. Overall, NBAL/BAL was not statistically associated with mortality at 28-30 days (RR, 0.85; 95% CI, 0.67-1.07; p = 0.169) or frequency of at least one SAE (RR, 1.15; 95% CI, 0.99-1.33; p = 0.059), compared with standard medical treatment. Subgroup results on ALF patients suggest possible benefit for mortality (RR, 0.67; 95% CI, 0.44-1.03; p = 0.069). From six reports of W-ECLP (12 patients), more than half (58%) of severe patients were bridged to transplantation and survived without transmission of porcine retroviruses. CONCLUSIONS: Despite no significant pooled effects of NBAL/BAL devices, the available evidence calls for further research and development of extracorporeal liver support systems, with larger RCTs and optimization of patient selection, perfusion durability, and treatment protocols.